Cereblon-binding proteins expression levels correlate with hyperdiploidy in newly diagnosed multiple myeloma patients - Kriegsmann, Katharina; Bärtsch, Marc-Andrea; Awwad, Mohamed; Merz, Maximilian; Hose, Dirk; Seckinger, Anja; Jauch, Anna; Becker, Natalia; Benner, Axel; Raab, Marc-Steffen; Hillengaß, Jens; Bertsch, Uta; et al. (Blood cancer journal, 2019)
Immunomodulatory drugs (IMIDs) are very effective in the treatment of multiple myeloma (MM). The description of their cereblon-mediated mechanism of action was a hallmark in MM research. Although the importance of IMID-induced degradation of cereblon-binding proteins is well described in vitro, the prognostic value of their expression levels in MM cells is less clear. Based on recently published data showing somewhat conflicting RNA levels, we analyzed the association between the levels of the Ikaros family zinc finger protein 1 (IKZF1), IKZF3, and karyopherin subunit alpha 2 (KPNA2) proteins measured by flow cytometry and prognostic parameters in 214 newly diagnosed MM patients who were randomized in the GMMG HD6 trial. No statistically significant associations between the expression levels and age, gender, light chain type, International Staging System (ISS) stage or cytogenetic high- and normal risk groups could be identified. Hyperdiploid MM cells expressed significantly higher levels of IKZF1, IKZF3 and KPNA2 than nonhyperdiploid cells. In contrast, translocation t(11;14) was associated with significantly lower expression levels. In conclusion, the observed overexpression of cereblon-binding proteins in MM cells with gain of chromosomes 5, 9, 11, 15, and 19 is consistent with the previously proposed positive regulation of MYC by IKZF1 and IKZF3, as well as MYC activation in hyperdiploid MM cells.